International syndicated loans - McDonald, Robert P. (London : Euromoney, 1982)
International syndicated loans have become the predominant financing vehicle for many borrowers required to raise larg amounts of debt in a relatively short-time. The first consortium loans, now more commonly known as syndications, can be traced to bankers of the Middle Ages, who often distributed financing risks among severa; houses to support trade flows, The modern version has a much shorter pedigree, and has only gained prominence as an established and reliable financing vehicle over the past 15 years.
Includes bibliographical references and index.
oif 10/04/2019
Loans
Keywords: Bank loans; Loans, Foreign; Crédits roll-over.